Exact solutions of (1+1)-Dimensional Kaup-Kupershmidt equation (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, we have obtained new analytical solutions of Kaup-Kupershmidt equation by using one method. We conclude that One method present a wider applicability for managing nonlinear partial differential equation. The solutions obtained in this paper are new.